Peningkatan Hasil Belajar Siswa Kelas II SDN 1 Gribig Untuk Tema 2 Subtema 1 : Bermain Di Lingkungan Rumah Dengan Menggunakan Metode Example Non Example - Sri Noor Widayati (Journal Prakarsa Paedagogia, 2018)
Education is the role important in human life. With education, human development in all aspects can influence to each other. The learning process can be carried out in various environments, one of which is school. The process of implementing learning carried out with reference to Curriculum 2013 has begun. However, student learning outcomes are still relatively low. This is due to a problem such as the condition of students who are less active during the lesson. This condition occurs mainly in the subject matter 2 about playing in my environment, sub theme 1 is playing in the home environment, in class 2 of the academic year 2018/2019. Based on this condition, the researcher intends to conduct a research activity in the form of a Class Action Research (CAR) by taking material in Theme 2 Sub Theme 1 which will be applied to grade 2 SDN 1 Gribig students with the Example Non Example method. CAR results using the Example non Example method proved to be able to increase student learning outcomes by 89% through two cycles, namely 31 students experienced an increase in learning outcomes from the total number of students in class II, namely 35 students.